Functional role of crosslinking in alginate scaffold for drug delivery and tissue engineering: A review - GÜNDÜZ, OĞUZHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The actual tendency exhibits continuous increment to use alginate polysaccharides in drug delivery and tissue engineering fields due to its attractive properties. Alginate pH-sensitiveness and its fabrication techniques have been extensively reported in the literature. However, in this review, the essential role of crosslinking process in the scaffold design will be highlighted. We discuss the possibility to use a different type of crosslinking to create proper biomimetic alginate hydrogels, emphasizing the possibility to improve alginate mechanical properties through chemical modification by covalent crosslinking or ionic combination with other polymeric materials. At the same time, the relevance of the degradation process and biocompatibility in these applications is also detailed described.
Keywords: Alginate; Crosslinking; Wound healing; Drug delivery; Tissue engineering; Biocompatibility; IN-VITRO; PHOTOCROSSLINKED ALGINATE; BIOMEDICAL APPLICATIONS; MECHANICAL-PROPERTIES; SODIUM ALGINATE; BONE-FORMATION; HYDROGELS; CELL; DESIGN; VIVO